Shifting towards the institutional language?: Predictors of parental institutional language exposure efforts. Issue 2 (1st October 2022) - Hollebeke, Ily; Agirdag, Orhan; Struys, Esli
Abstract : Early on, parents in multilingual families start moulding their children's linguistic environment, a process which is believed to be influenced by several external and family-related factors. The present study examines which factors correlate with parents' efforts to maximise the institutional language (here Dutch) input in the home. The variables taken into account are: the families' language policy constituted by language practices, beliefs and management; advice from both early childhood professionals and other sources; the parents' linguistic and educational resources, as well as the family's migration generation. Our data, representing 776 multilingual families in the officially monolingual, yet de facto language-diverse Flemish community of Belgium, were subjected to a bivariate correlational analysis and a stepwise logistic regression. Our results show the potential influence of advice and educational resources on parental decisions to maximise their children's institutional language input. Both lower educational resources and advice given by professionals are linked with higher Dutch exposure efforts, whereas advice from other sources appears connected with less inclination to expose children to the institutional language at home. In further discussing our findings, policy implications are introduced.